Web Platform for Romanian SMEs Networking - Bucea-Manea-Tonis, Radu; Tonis (Bucea-Manea), Rocsana (Journal of Economic Development, Environment and People, 2016)
Abstract. After the 90s, private initiative in Romania has tried to get market shares in the emerging niches: IT services, ecommerce, retail, energy. With the liberalization of the market after admission to the EU, local entrepreneurs could not cope with external competition, crushing in debts or insolvency. The situation is not different today when the local capital is strongly competed by multinational companies. After a continuous research process the conclusion is the only solution for the SMEs is collaboration in business hubs, virtual companies and other forms of local cooperation. In this article is presented a type of collaboration between SMEs using discount coupons to recommend each other clients.